Amateur Village Drama and Community in England, 1900–1950. (August 2022) - Wallis, Mick
Abstract : In the interwar period, amateur drama was actively promoted as a means to create or repair, sustain and develop community consciousness in English villages. In this article, Mick Wallis maps such promotion across various fields of practice at their intersection with the village drama 'movement' as a field itself. These include gentry patronage, post-war and rural reconstruction, adult education, and women's self-advancement. He also charts the emergence of interwar village drama from its precursors since 1900, and the emergence from it of the system of local government Drama Advisers that persisted until the 1990s. Time and again, drama is presented as a vital tool in the improvement of the lives of individuals, the development of national citizens, and the restoration and celebration of local communities. Finally, he suggests the important insights that this work can offer future researchers. Mick Wallis is Professor Emeritus of Performance and Culture at the University of Leeds.